KIYMETLİ EVRAKIN ZİYAI VE İPTALİ - (:unkn) unknown (My University, 2017)
6102 sayılı Türk Ticaret Kanunu'nda kıymetli evrak niteliği taşıyan senetlerin iptali 651-652/2 hükümlerinde genel olarak düzenlenmiştir. Kanun'un 652/2 ve 653 hükümlerinde kıymetli evrakın çeşitli türleri (nama, emre ve hamiline) ile çeşitli kıymetli evrakın iptal usulleri ve sonuçları hakkında, özel hükümler saklı tutulmuştur. Bu çalışmada kıymetli evrakın ziyaı ve iptaline ilişkin yeni hükümlerin uygulanma alanı, kapsam ve sınırları, çeşitli sorunlara ağırlık verilmek suretiyle incelenmiştir.

The annulment (cancellation) of notes that are defined as negotiable instruments has been governed in general by articles 651 and 652/2 of the Turkish Commercial Code No. 6102. Special provisions related to the types of negotiable instruments (Payable to the name of, Payable to Order, Payable to Bearer) and ways and results of the annulment of different types of negotiable instruments take place in articles 652/2 and 653 of the Code. This paper studies the practice areas, scope and limitations of the new provisions of the Turkish Commercial Code related to the loss and annulment of negotiable instruments with an emphasis on various problems encountered.
LOSS AND ANNULMENT (CANCELLATION) OF NEGOTIABLE INSTRUMENTS
Keywords: Hukuk